Enhancing students’ digital learning experiences across cultures - Martins, Maria de Lurdes (2017)
The challenges of multiculturalism and multimodal forms of communication have brought to the fore the need to (re)examine the way English as Foreign Language (EFL) is taught and learned. This no longer seen as the sole responsibility of educational institutions but as a life-long process arising from learning through personal and professional experience and through various channels. This paper reports on a telecollaboration project - European Dialogue Project (EDP) - and examines mutual contributions of Web 2.0 technologies and EFL to each other, and the challenges in designing and implementing collaboration projects across cultures. In order to become competent communicators in collaborative technology mediated projects, students need not only to develop some technical skills, allowing them to know how to use the different tools, but also be familiar with a range of social practices and behaviours associated with collaborating online. The challenge is, undoubtedly, to promote these skills and attitudes in parallel with teaching EFL. In the EDP, students, working in international teams, had to discuss and compare the values shared by young people in Italy, Portugal, Germany and France, being in charge of designing and carrying out a collaborative survey to assess students’ views on specific topics The aim of the project was encouraging autonomous communication in English, also sensitising them towards digital global communication practices in real-life scenarios.